PYGMALION GOLD AWARD 2012 - Mouzouropoulos, Theseas (My University, 2026)
The award was received by the Creative Club of Cyprus member of the Art Directors Club of Europe (ADCE)for exemplary design and concept in the category Graphic Design. The concept of the ICSVC Applications designed for the ICSVC Conference is based on the multimodal nature of Typography, having two sign systems juxtaposed together for communication; the Braille and the Visual, combined with customized letter-forms for a simultaneous ‘touch-and-see’ interpretation of the message.
Keywords: Arts and entertainment